Sejarah Maritim di Nusantara (Abad VII-XVI): Interkoneksi Kerajaan Sriwijaya, Majapahit, dan Demak - Mochammad Nginwanun Likullil Mahamid (Historia Madania: Jurnal Ilmu Sejarah, 2023)
Archipelago, the main theme of this article, is a term for a region known as Southeast Asia today, especially the countries with similar historical events about ancient rulers, such as Indonesia, Malaysia, Singapore, Thailand, Vietnam, Cambodia, and others. Thus, the writing of this article was directed at reviewing material related to the existence of rulers, especially those engaged in the maritime field in the archipelago, with a focus on discussion on three subjects, including Sriwijaya, Majapahit and Demak, and was selected on the basis of similarities in historical events. The method used was descriptive analysis through books and other written materials, such as journal articles and seminar proceedings. Then, a written description of the reading and an unwritten description of the material in the form of photos/pictures were added. Lastly, the analysis was carried out using the concept of “Total History” proposed by Fernand Braudel. In this concept, there were three historical facts in one period, namely events, conjuncture, and structure. The findings of this article explained the development of the three maritime rulers of the archipelago, including the Srivijaya Kingdom (VII-XIII centuries), Majapahit Kingdom (XIII-XV centuries), and Demak Kingdom (XV-XVI centuries), which referred to the concept as an internal event empire since its inception, heyday, and decline. In addition, the interconnection of the three kingdoms was the existence of the side of the descendants of the previous kings and the enthusiasm for building the civilization of the archipelago, which was passed on to the rulers afterward through strengthening in the maritime sector.